Assessing the impact of COVID-19 and related interventions on poverty and economic growth in Pakistan: A structural path analysis - Davies, Stephen; Quershi, Tehseen; Rana, Abdul Wajid; Haider, Zeeshan; Raja, Sehrish (Wiley, 2023)
This study uses social accounting matrix multipliers and structural path analyses to estimate effects of COVID-19 and related fiscal stimuli on five household groups. The COVID-19 lockdown increased poverty in Pakistan by 15%, which was addressed using a $1.5 billion, digitally implemented Ehsaas Emergency Cash (EEC) program that reached 14.8 million poor households. The study's models show that the largest multipliers from Ehsaas program finance were in agriculture, as a 1 Rupee shock adds 0.225 Rupee income to households. About 30% of that gain was estimated to go to poor farm families. In contrast, our models find that construction and trade growth added three times as much income to poor nonfarm and urban households as to farm households. However, those sectors added only one third as much total income as agriculture. From the structural path analysis, the importance of capital assets in generating income was seen, as was the possibility of greater poverty reduction from sectors with proportionally fewer intermediate inputs and more value added.